Proceedings of the International Conference on Knowledge Management and Information Sharing 2014
DOI: 10.5220/0005077702120219
|View full text |Cite
|
Sign up to set email alerts
|

Should I Be Aware of the Information of Other Actors - Transversal Communication in Crisis Management

Abstract: In crisis management, multi-organizations are involved to deal with the events; however these services encounter several problems that make the transversal communication and information sharing very hard, with an ineffective mutual awareness during crisis response. Whereas, among the factors for crisis management success, figures prominently mutual awareness and awareness information, this requires effective interaction of the relevant information between emergency actors. But in the reality this communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Marcella and Lockerbie (2016) found that the managers of offshore oil and gas installations engaged in two forms of information behavior during ordinary and crisis time: maintaining safe operations, and reacting to a rapidly changing emergency situation during crises. Much of the scholarship considers aspects of the collaborative information practices of members of multidisciplinary communities of practice (Taber and Taber 2013), e.g., trust and respect (Sonnenwald et al 2014), awareness, and coordination of activities (Heath and Luff 1992, Sarcevic 2007, Saoutal, Matta, and Cahier 2014. Westbrook (2009) conceptualizes "crisis" in a less immediate way, focusing on everyday information needs within three progressive stages of leaving an abusive partner: considering a change from an abusive situation, adjusting to change (involvement with shelter/police); and preparing for life after the change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marcella and Lockerbie (2016) found that the managers of offshore oil and gas installations engaged in two forms of information behavior during ordinary and crisis time: maintaining safe operations, and reacting to a rapidly changing emergency situation during crises. Much of the scholarship considers aspects of the collaborative information practices of members of multidisciplinary communities of practice (Taber and Taber 2013), e.g., trust and respect (Sonnenwald et al 2014), awareness, and coordination of activities (Heath and Luff 1992, Sarcevic 2007, Saoutal, Matta, and Cahier 2014. Westbrook (2009) conceptualizes "crisis" in a less immediate way, focusing on everyday information needs within three progressive stages of leaving an abusive partner: considering a change from an abusive situation, adjusting to change (involvement with shelter/police); and preparing for life after the change.…”
Section: Literature Reviewmentioning
confidence: 99%